To simplify the expression \( 8m^5(6m - 4m^2) \), we will distribute \( 8m^5 \) to each term inside the parentheses.
-
Distributing \( 8m^5 \) to the first term \( 6m \): \[ 8m^5 \cdot 6m = 48m^{5+1} = 48m^6 \]
-
Distributing \( 8m^5 \) to the second term \( -4m^2 \): \[ 8m^5 \cdot (-4m^2) = -32m^{5+2} = -32m^7 \]
Now, combining both results, we have: \[ 48m^6 - 32m^7 \]
We can rearrange this to write it in standard form: \[ -32m^7 + 48m^6 \]
Thus, the simplified form of the expression \( 8m^5(6m - 4m^2) \) is: \[ \boxed{-32m^7 + 48m^6} \]